Higher Taxes, More Evasion? Evidence from Border Differentials in TV License Fees - Melissa Berger; Gerlinde Fellner; Rupert Sausgruber; Christian Traxler (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper studies the evasion of TV license fees in Austria. We exploit border differentials to identify the effect of fees on evasion. Comparing municipalities at the low- and high-fee side of state borders reveals that higher fees trigger significantly more evasion. The central estimate from a spatial regression discontinuity design indicates that a one percent increase in fees raises the evasion rate by 0.3 percentage points. The positive effect of fees on evasion is confirmed in different parametric and non-parametric approaches and survives several robustness checks.
Keywords: H26; H27; 330; evasion; TV license fees; border tax differentials; regression discontinuity design